Akuntabilitas Dalam Pengelolaan Keuangan Daerah (Suatu Studi Pada Dinas Pendapatan Daerah Kabupaten Banggai Kepulauan) - Ludani, Melina Marcori; Tampi, Gustaf Budi; Pombengi, Jericho Denga (Sam Ratulangi University, 2015)
ABSTRACT: Accountability can live and thrive in a transparent and democratic atmosphere and the freedom to express opinions. And then, the government should really be aware the government and the public service is something can not be separated from the public. The realization of the region 's financial accountability will be the initial basis for governance better and all financial accountability that comes from public funds going smoothly as public confidence in the government in the field of financial management.This research used descriptive research through in-depth interviews to 23 informants, the data collection techniques using of observation, interviews and documentation. The resultAccountability system is one of the crucial points of the implementation of the regional administration. Accountability system is a systematic and continuous process for assessing the success or failure of governance and development activities in accordance with the policies, programs, goals, and objectives that had set in realizing the vision of the district as government of Banggai Islands set out in Medium Term Development Plan (RPJMD).The Conclusion isLocal governments is very trying to account for funds from the public for development and welfare of the communities in district of Banggai islands..Keywords: Accountability, Local Financial Management